Possibilities of radiotherapy in the treatment of pediatric Hodgkin’s lymphoma - Filipovic, Predrag (Medical Research, 2024)
Pediatric Hodgkin’s lymphoma is a malignant, lymphoproliferative disease of children and adolescents. Radiotherapy is an important form of treatment. The possibility of late toxicity of radiotherapy is a limiting factor in the application of radiotherapy as a treatment modality in pediatric patients. The technological progress of radiotherapy, the introduction of advanced radiotherapy techniques and proton therapy, has improved the precision of radiotherapy and reduced the risk of long-term consequences. These technologies enabled targeted treatment, significantly reducing the exposure of healthy tissues and organs to radiation. All existing treatment recommendations and conducted cooperative studies have shown that radiation therapy is effective in the treatment of pediatric Hodgkin’s lymphoma, especially when combined with chemotherapy. On the other hand, there is the possibility of late toxicity to organs in growth and development, as well as the occurrence of secondary malignancies, which must be carefully considered when deciding on the implementation of radiotherapy. Radiation therapy represents an important therapeutic approach in the combined treatment of pediatric Hodgkin’s lymphoma. The combined therapeutic approach has improved treatment results, and advanced radiotherapy techniques will reduce the risk of side effects. Indications for the use of radiotherapy should be carefully evaluated in the treatment of pediatric patients with Hodgkin’s lymphoma. Key words: pediatric Hodgkin’s lymphoma, radiation therapy, combined treatment, toxicity